Anion binding by calix[4]arene ferrocene ureas - Evans, A; Matthews, SE; Cowley, A; Beer, P (2003)
A ferrocene reporting unit has been successfully incorporated onto the upper-rim of calix[4]arenes through either urea or amide hydrogen bonding units for the preparation of three novel receptors which can sense the binding of anions electrochemically. 1H NMR studies indicate that the receptors have a general preference for binding more basic anions, and in the case of the tetra-urea derivative, a marked selectivity for dihydrogen phosphate. A single crystal X-ray structure of the di-urea derivative reveals the role of hydrogen bonding interactions in the binding of benzoate. Cyclic and square wave voltammetric studies demonstrate that all receptors can electrochemically sense the binding of anions with dihydrogen phosphate inducing the largest shifts.